Algorithm of development for system operation monitoring of water-soluble bases in hydraulic structures - K. P. Latyshenko; T. N. Nurmagomedov (Омский научный вестник)
The article discusses algorithm of development of the monitoring system operation for water-soluble bases of a hydraulic structures based on the conductometric control method using special technical measuring instruments. The structure of the information system for monitoring water-soluble bases of hydraulic structures is presented. A mathematical description of the monitoring method based on the conductometric control method is carried out. A general algorithm for the information system operation and an algorithm for polling conductometric sensors have been developed. An adaptive algorithm for polling sensors is proposed, which allows changing the polling period depending on the level of threat of an emergency.